Partial characterization of jumbo squid skin pigment extract and its antioxidant potential in a marine oil system. Issue 9 (18th January 2016) - Aubourg, Santiago P.; Torres‐Arreola, Wilfrido; Trigo, Marcos; Ezquerra‐Brauer, Josafat Marina
Abstract : Pigment compounds were extracted from jumbo squid ( Dosidicus gigas ) skin with an acid‐ethanol solvent (JSE). Freeze‐dried JSE was characterized with respect to solubility in different solvents, absorption UV–VIS, and FT‐IR spectra, and tested for its radical scavenging activity against ABTS and oxygen radical absorbance capacity (ORAC). The potential ability of JSE for inhibiting oxidation of cod liver oil (CLO) was also determined by monitoring dienes, trienes, peroxide value (PV), thiobarbutiric acid (TBA), and polyene index (PI) in samples stored at 15, 25, and 50° C for 12 days. Concentrations of 0, 0.1, 0.5, 1, and 2% JSE were added to CLO. The yield of JSE was 8.8 mg/g freeze‐dried skin. Solubility behavior, UV–Vis, and FT‐IR spectra of JSE suggests that this pigment extract might belong to the ommochrome family. Moreover, a characteristic xanthommatin peak (1740 cm −1 ) was observed. JSE exhibited scavenging activity on ABTS + radical and in the ORAC assay. After storage PV and TBA increased, whereas PI decreased mainly in the control treatment. The addition of JSE delayed lipid oxidation in CLO during the first 8 days of storage at 50° C. JSE was identified as promising source of antioxidants to retard fish lipid oxidation. Practical applications : This study demonstrates that acid‐ethanol pigment extract from jumbo squid skin, which is a by‐product generated by the squid processing industries, is a valuable antioxidant source. Consistent with the preservative effect observed for this pigment extract, squid skin may be successfully employed to obtain new products for food processing and the pharmaceutical industry, with environmental sustainability benefits and provide a more effective use for jumbo squid by‐products. Acid‐ethanol pigment extracts from freeze‐dried jumbo squid skin (JSE) were added to cod liver oil and stored at 50°C. Increasing levels of JSE (0 < 0.1 < 0.5 < 1 < 2%) led to less lipid oxidation. JSE likely belongs to the ommochromes family. Abstract : Acid‐ethanol pigment extracts from freeze‐dried jumbo squid skin (JSE) were added to cod liver oil and stored at 50°C. Increasing levels of JSE (0 < 0.1 < 0.5 < 1 < 2%) led to less lipid oxidation. JSE likely belongs to the ommochromes family.